Those wonderful women in their flying machines : the unknown heroines of World War II - Keil, Sally Van Wagenen (New York : Four Directions Press, 1990)
The story of over 2,000 women pilots who joined the WASP where they flew everything in the Army Air Forces aircraft inventory.
Includes index.
Donated by Ruth Florey.
Keywords: World War, 1939-1945 -- Participation, Female; Air pilots, Military -- United States; Women Airforce Service Pilots (U.S.); Women in aeronautics -- United States; World War, 1939-1945 -- Aerial operations, American